SCHOOL CLIMATE INFLUENCING JOB SATISFACTION OF TEACHERS IN PRIVATE PRIMARY SCHOOLS IN CHANMYATHAZI TOWNSHIP, MANDALAY, MYANMAR - Ko Ko, Darle (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2024)
Abstract: This study aims to identify the influence of the school climate on teachers’ job satisfaction in private primary schools in Chanmyathazi township, Mandalay, Myanmar. The research objectives were to determine the school climate (condition of facilities, academic climate, colleague support and principal leadership), to examine the teachers’ job satisfaction and to identify the influence of the school climate on teachers’ job satisfaction. The research employs a quantitative research approach to achieve its objectives. To collect data for the study, the purposive sampling was applied and 45 participants who were both full-time and part-time teachers from the selected schools in the research. All of the participants provided responses, resulting in a 100% response rate. The research instruments were taken from the previous researches. The Multiple Linear Regression was applied for data analysis. The result revealed that there was an influence between school climate and teachers’ job satisfaction with the p value of <.001 and R-squared was .567 or 56.7%. The academic climate was the most influential component towards teachers’ job satisfaction with the Beta value of .704 or 70.4% at p<.001. The study would recommend the private primary schools to analyze upon the perspectives that enhance school climate to ensure teachers’ job satisfaction.